Maternal exercise represses Nox4 via SIRT1 to prevent vascular oxidative stress and endothelial dysfunction in SHR offspring - Zhang, Yanyan; Shan, Meiling; Ding, Xiaozhen; Sun, Hualing; Qiu, Fang; Shi, Lijun (Frontiers in Endocrinology, 2023)
Maternal exercise during pregnancy has emerged as a potentially promising approach to protect offspring from cardiovascular disease, including hypertension. Although endothelial dysfunction is involved in the pathophysiology of hypertension, limited studies have characterized how maternal exercise influences endothelial function of hypertensive offspring.In this study, pregnant spontaneously hypertensive rats and Wistar-Kyoto rats were assigned either to a sedentary lifestyle or to swimming training daily, and fetal histone deacetylasemediated epigenetic modification and offspring vascular function of mesenteric arteries were analyzed. Maternal exercise ameliorated the impairment of acetylcholine-induced vasodilation without affecting sodium nitroprusside-induced vasodilation in mesenteric arteries from the hypertensive offspring. In accordance, maternal exercise reduced NADPH oxidase-4 (Nox4) protein to prevent the loss of nitric oxide generation and increased reactive oxygen species production in mesenteric arteries of hypertensive offspring. We further found that maternal exercise during pregnancy upregulated vascular SIRT1 (sirtuin 1) expression, leading to a low level of H3K9ac (histone H3 lysine 9 acetylation), resulting in the transcriptional downregulation of Nox4 in mesenteric arteries of hypertensive fetuses. These findings show that maternal exercise alleviates oxidative stress and the impairment of endothelium-dependent vasodilatation via SIRT1-regulated deacetylation of Nox4, which might contribute to improved vascular function in hypertensive offspring.